Ukraine : 2003 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Ukraine. (IMF Staff Country Reports; Country Report ;, 2003)
This 2003 Article IV Consultation highlights that real GDP of Ukraine grew by more than 4 1\2 percent in 2002, marking the third year of Ukraine's economic expansion following the 1998/99 financial crisis. As in 2001, growth was not only supported by robust consumer spending, reflecting large wage increases, but also by an increase in net external demand. Consumer price inflation fell to near zero in 2002, reflecting primarily the good harvests in 2001/02 and the resulting sharp drop in food prices. Low inflation was also supported by a tightening of fiscal policy and delays in increasing administered prices.